On the Question of the Semantic-Functional Relationship between the Two Forms of the Subjunctive in Classical Armenian - Avetyan, Sargis (History and Culture, 2022)
It is argued that attempts to characterize the semantic relationship between the two forms of the Subjunctive (the present subjunctive and the aorist subjunctive) in Classical Armenian as either a mood contrast or an aspect-mood contrast are not backed up by the relevant synchronic as well as diachronic linguistic data of Old Armenian. The nearly identical syntactic functions of the two forms of the Subjunctive in Classical Armenian, along with their diachronically similar morphological structure (owing to the addition of one and the same suffix *-ից to either the present stem or the aorist stem), leaves no doubt that the both forms under consideration are subjunctive-mood forms. As to the difference in the frequency of use of the two forms of the Subjunctive in Classical Armenian, it should be accounted for by the general diachronic tendency for the present subjunctive to get restricted in use and displaced gradually by the aorist subjunctive. On the other hand, a detailed contextual-semantic analysis of uses of the present subjunctive and the aorist subjunctive in Classical Armenian, clearly testifies to the original aspectual (imperfective - perfective) contrast between them. However, it is also evident that the aspectual contrast had already ceased to be conceived of as a living grammatical phenomenon in the case of the Subjunctive in Classical Armenian and therefore did not manifest itself in a regular way: in aspectual terms identical actions/events were often expressed both by the present subjunctive and the aorist subjunctive. Moreover, they could even occur side by side within one and the same sentence.